Common and Antarctic Minke Whales: Conservation Status and Future Research Directions - Risch, Denise; Norris, Thomas; Curnock, Matthew; Friedlaender, Ari (Frontiers in Marine Science, 2019)
Minke whales comprise some of the most widely distributed species of baleen whales, some of which are still regularly targeted by commercial whaling. Here, we review the conservation status of common (Balaenoptera acutorostrata) and Antarctic (Balaenoptera bonaerensis) minke whale populations, against the backdrop of ongoing whaling operations and other anthropogenic threats, including climate change, entanglement in fishing gear, ship strikes and noise pollution. Although some coastal minke whale populations have been studied in detail, others, which inhabit remote and ecologically sensitive locations, such as the Antarctic ice shelf, are among the least understood populations of marine mammals. The unresolved taxonomy of dwarf minke whales further highlights some of the existing knowledge gaps concerning these species. Due to their relatively small size and elusive behaviours, large uncertainties exist for almost all minke whale populations with respect to behaviour, migratory routes and winter distributions, hindering effective conservation and management. However, recent advances in research technology, such as passive acoustic monitoring (PAM), unmanned aerial systems (UAS), multisensor recording tags, and machine learning assisted photo-identification, are increasingly being applied to study minke whales and their habitat, and are starting to open new windows into their life history and ecology. In future research, these non- and less-invasive methods should be integrated in larger-scale comparative studies aiming to better understand minke whale behaviour, ecological interactions and their varying habitats to drive and support effective species conservation.